Last dance, last chance and other true cases (New York Pocket Books, 2003)
The title case is an account of the life and crimes of Dr. Anthony Pignataro, a cosmetic surgeon with a penchant for forged credentials, botched surgeries, to the attempted arsenic poisoning of his wife. Four other true cases follow.
A note on liars -- Last dance, last chance -- The accountant -- The killer who begged to die -- The beach -- The deperate hours.
Keywords: Crimes of passion -- Case studies; Criminals -- United States; Family violence -- Case studies; Murder -- United States -- Case studies; Offenses against the person -- Case studies